The peyote effect : from the Inquisition to the War on Drugs - Dawson, Alexander S. (Alexander Scott), 1967- (University of California Press, 2018)
"Banned by the Inquisition in 1620, peyote was implicated in over 80 religious trials during the colonial period. After four centuries of change, we have arrived at the beginning of the 21st century to a point where our laws concerning peyote resonate uncomfortably with the laws promulgated by the Spanish Inquisition. The justifications are different, and in part it seems like a quirk of history, this book pursues the question of whether laws the Mexican and US governments have created in the 20th and 21st centuries in some ways repeat a colonial tradition in which indigenous bodies were made incommensurable with non-indigenous bodies through the legal and social proscriptions enacted around peyote. The book seeks to understand how it was that peyote came to be so closely identified as an Indian thing even as other plants and animals native to the Americas lost their indigenous essence. In the final six chapters of the book we see how peyote was simultaneously embedded in four distinct phenomena: a taxonomic project concerned with making sense of psychedelic substances as drugs, a counter-cultural movement which saw in peyote an opportunity to embrace alternative forms of consciousness, a conservative movement that understood peyote as one of a number of existential threats to civilization, and burgeoning movements for indigenous self-determination that saw in peyote a powerful expression of indigenous alterity"--Provided by publisher.